Selenium Nanoparticles Synergistically Stabilized by Starch Microgel and EGCG: Synthesis, Characterization, and Bioactivity - Jiaojiao Zhou; Yuantao Liu; Yili Hu; Die Zhang; Wei Xu; Lei Chen; Jiangling He; Shuiyuan Cheng; Jie Cai (Foods, 2022)
Selenium (Se) is a chemical element essential to human health because of its bioactive properties, including antioxidative, anticancer, and immunomodulating activities. Despite the high therapeutic potential of Se, its intrinsic properties of poor stability, a narrow therapeutic window, and low bioavailability and bioactivity have limited its clinical applications. Selenium nanoparticles (SeNPs) exhibit lower toxicity and higher bioactivity than other Se forms. Herein, we report a green method for the preparation of monodisperse SeNPs with starch microgel (SM) and epigallocatechin gallate (EGCG) through Se-O bonds and polysaccharide–polyphenol interactions (namely, SM-EGCG-SeNPs). SM-EGCG-SeNPs showed higher stability, bioactivities, and cytotoxicity than SeNPs and SM-SeNPs at the equivalent dose. SM-EGCG-SeNPs induced the apoptosis of cancer cells via the activation of several caspases and reactive oxygen species overproduction. This work proposes a facile method for the design and potentiation of structure-bioactive SeNPs via polysaccharide–polyphenol interactions.